Learning Dynamics in Tax Bunching at the Kink: Evidence from Ecuador - Albrecht Bohne; Jan Sebastian Nimczik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
"Learning Dynamics in Tax Bunching at the Kink: Evidence from Ecuador", Albrecht Bohne and Jan Sebastian Nimczik
Keywords: H24; H26; D83; 330